Efektivitas Regulasi Pengawasan Pemerintah Indonesia dan Malaysia dalam Mencegah Penipuan Perjalanan Travel Umrah - Arina Saidah Putri (Universitas Muhammadiyah Gresik, 2026)
This research examines the effectiveness of government regulations and supervision in Indonesia and Malaysia in preventing umrah travel fraud. The prevalence of umrah fraud cases in both countries indicates fundamental problems in the supervision system and consumer protection. In Indonesia, the First Travel and Abu Tours cases demonstrate weak supervision implementation despite existing regulations. Meanwhile, Malaysia with its centralized system through Tabung Haji shows a better level of effectiveness. This research employs a normative juridical method with a comparative law approach, analyzing regulations and policies in both countries through literature study of primary and secondary legal materials. The findings reveal that although Indonesia has a comprehensive legal framework through Law Number 8 of 2019 and Minister of Religious Affairs Regulation Number 5 of 2021, its effectiveness remains weak due to unintegrated supervision systems, limited resources, and minimal control over pilgrim fund management. Conversely, Malaysia with its centralistic approach, strict law enforcement, and information transparency has been more successful in reducing fraud cases. The Indonesian government has undertaken various improvement efforts such as strengthening licensing, developing the Siskopatuh application, establishing special pilgrim fund accounts, intensifying field supervision, and public education campaigns, yet new challenges continue to emerge with digital technology development.